Analysis Of Financial Performance At Communication And Informatics Department In Bengkulu Selatan District - Noni Lestari; Ahmad Soleh; Suswati Nasution (Journal of Indonesian Management, 2023)
The performance of government agencies is now in the spotlight with increasing public awareness of the implementation of public administration. Society often views public sector organizations as nests of inefficiency, waste, sources of leakage of funds and institutions that always lose money. The purpose of this study was to determine the financial performance of the Communication and Informatics Service in South Bengkulu Regency.This study uses a quantitative research approach, collecting data using secondary data search, data analysis. The results of this study indicate that the financial performance of the South Bengkulu District Communication and Informatics Service for 2018-2022 based on the degree of decentralization ratio is in the very low category. Then based on the regional financial dependency ratio, experiencing a low level of dependence on the central government in providing transfer funds. Based on the ratio of regional financial independence, experiencing a very low level of independence. Based on the compatibility ratio, namely the ratio of regional financial operating expenditures, experienced a fairly low portion of operating expenditures due to the lack of revenue from the South Bengkulu Regency Communication and Informatics Office.